Procedural sedation at role 1: applicability to military clinicians and minimum monitoring criteria. Issue 2 (5th March 2020) - Ellington, Matt; Booker, R J
Abstract : Procedural sedation is defined as producing a state of reduced consciousness, where the patient is still able to respond to verbal or physical stimulus and to continuously maintain a patent airway and adequate ventilation. This can be done to facilitate treatment that would not be otherwise possible. Recent evidence, guidelines and new equipment introductions have improved the safety of procedural sedation at UK role 1 medical treatment facilities (MTFs). A role 1 MTF is defined by the North Atlantic Treaty Organization as a medical facility focusing on the provision of primary healthcare, specialised first aid, triage, resuscitation and stabilisation, and is usually staffed by a general practitioner or a general duties medical officer. This paper aims to update role 1 clinicians on the current evidence base and guidance regarding monitoring of patients during procedural sedation.